Pengolahan Air Bersih di Pondok Pesantren As – Shiddiqiyyah dan Panti Asuhan Al-Haq Kecamatan Sungai Kakap Kabupaten Kubu Raya - Eka priadi; Johnny Maruli Tua Sitompul (Universitas Muhammadiyah Pontianak, 2018)
As – Shiddiqiyyah Boarding School and Al-Haq orphanage have shortage of clean water. Both of partners used well water for bathing, washing and latrines (MCK). Well water quality is bad because it contains high iron content. Therefore, a water treatment plant is needed that is capable of processing well water so it is safe to use. Water treatment design consists of aeration, adsorption, and filtration. The processing capacity is 1100-1550 liters. The method is a parcipatory and collaborative method whereby santri and orphanage children participate in activities such as socialization and training, operation and maintenance of clean water treatment plants. In addition, the water treatment guidebook is designed to facilitate the operation and maintenance of clean water installations. PKM runs smoothly and partners have high amino activity. The evident from the positive partner response and good communication between the participants and the team of devotion.